Prevalence of antibodies against Lawsonia intracellularis in dogs with and without gastrointestinal disease - J. Klimes; K. Dezorzova; J. Smola; R. Husnik (Veterinární Medicína, 2007)
Blood sera from 71 dogs were examined for specific IgG antibodies against Lawsonia intracellularis using the indirect immunofluorescent antibody test. The dogs were divided into two groups according to the presence or absence of gastrointestinal disease, which could potentially be associated with L. intracellularis. In the group of dogs with gastrointestinal disease (n = 54), 40 dogs were positive (74.1%). Most positive dogs suffered from chronic or intermittent diarrhoea. In the group without signs of primary gastrointestinal disease (n = 17), antibodies were found in 13 dogs (76.5%). The overall positivity was 74.7%. These results indicate that dogs may be an important host species of L. intracellularis.